Dispatching concrete trucks using simulation method - Biruk, Sławomir (Budownictwo i Architektura / Civil and Architectural Engineering, 2015)
Ready mixed concrete (RMC) is the primary material required for buildings and public infrastructure work. RMC is produced to meet customer’s demands and its deliveries must conform to construction site and technological operating constraints – the material cannot be prepared in advance and stored. Concrete production scheduling and truck dispatching is mainly handled manually by experienced RMC batching plants staff. The paper presents simulation model which can be used to asses alternative strategies for truck allocation and production planning in stochastic environment. The models’ operation is illustrated by a notional case – the model prompted solutions of improved transhipment efficiency and reduced plant operating cost under assumed operating constraints.